2004
DOI: 10.4049/jimmunol.173.6.4020
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 Activates a Mechanism of Tissue Fibrosis That Is Completely TGF-β Independent

Abstract: Fibrosis is a characteristic feature in the pathogenesis of a wide spectrum of diseases. Recently, it was suggested that IL-13-dependent fibrosis develops through a TGF-β1 and matrix metalloproteinase-9-dependent (MMP-9) mechanism. However, the significance of this pathway in a natural disorder of fibrosis was not investigated. In this study, we examined the role of TGF-β in IL-13-dependent liver fibrosis caused by Schistosoma mansoni infection. Infected IL-13−/− mice showed an almost complete abrogation of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
244
3
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(279 citation statements)
references
References 80 publications
20
244
3
6
Order By: Relevance
“…One possible explanation is the failure to transition from a Th1 type of response to a Th2 type of response, as has been proposed by a number of recent fibrosis models (28,31,34). Consistent with this possibility are studies that implicated CD204 involvement in the regulation of IL-12 release from AM (7,30).…”
Section: Discussionsupporting
confidence: 62%
“…One possible explanation is the failure to transition from a Th1 type of response to a Th2 type of response, as has been proposed by a number of recent fibrosis models (28,31,34). Consistent with this possibility are studies that implicated CD204 involvement in the regulation of IL-12 release from AM (7,30).…”
Section: Discussionsupporting
confidence: 62%
“…Studies in a variety of systems have demonstrated that IL-13 is a major mediator of these fibrotic responses (42,51,56). A number of studies demonstrated that IL-13 causes tissue fibrosis, at least in part, by inducing and activating TGF-␤1 (22,32), which is dependent on MCP-1/CCL2 and MMP-9, respectively (30,32).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, at this stage, despite granuloma involution as eggs are killed and the development of hyporesponsiveness in Th2 cells [47], the Th2/M2 inflammatory response elicits tissue remodelling, including induction of matrix metalloproteinases (MMPs), tissue inhibitor of metalloproteinases (TIMPs) and collagens, that culminates in life-threatening liver and intestinal fibrosis, portal hypertension and haemorrhages (16-20 wkpi) [28,38,41,[48][49][50]. IL-13, via the IL-13Rα1/IL-4Rα receptor, is the most important fibrotic agent in schistosomiasis, with additive effects of IL-4, IL-5, IL-10 and IL-21 but not of TGFβ [45,[50][51][52][53]. Consequently, distinct collaborative IL-13 regulatory pathways that suppress the Th2/M2 activation and hamper fibrosis progression have been identified: the high-affinity IL-13 decoy receptor (IL-13Rα2) expressed by stromal cells; IL-12/IL-23p40 produced by macrophages and DCs driving the Th1/Th17 response; and IL-10 produced by M2 and regulatory T cells [46,[54][55][56][57][58][59].…”
Section: Host Immune Response Determines the Pathogenicity Of Schistomentioning
confidence: 99%